Archivarbeit im Wandel Das Beispiel des preußischen Staatsarchivs in Schleswig-Holstein 1870-1947 - Schmidt, Sarah (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2021)
History is written in archives, but archival work itself is also subject to change over time. Using the Prussian State Archives in Schleswig-Holstein as an example, this process is examined over the period of its existence from 1870 to 1947. The focus is on the changes in the core tasks, i.e. how the process of evaluating documents changed, what challenges the storage of archival records offered and how much the use of the archive fluctuated. The question of the extent to which individual influences played a role is also emphasized. The other Prussian state archives are used as a comparison. In addition, due to the close historical connection, the relations with Denmark are illuminated.